Caractérisation morphologique de colletotrichum gleosporioides et colletotrichum sp. , responsables de l’anthracnose des agrumes à Mostaganem et spécialisation parasitaire du pathogène. - YSSAAD, Halima; MEDAOUAR, Zahra (My University, 2018)
This study aims at morphological and pathogenic characterization of Colletotrichum gloeosporioides and colletotrichum sp. responsible for citrus anthracnose in the area of Bouguirat, Mostaganem region and to identify the species or species of Colletotrichum causing this disease. Our study is conducted on eight isolates of Colletotrichum; five belong to C. gloeosporioides named Ti1, Ti2, Fi2, Fi3 and Fi5 and are obtained, during the year 2015, from stems and leaves of the species Thomson Navel, the others are isolated in March 2018 from clementine leaves and are named CF13, CF12 and CF2. All samples are taken from the same field, located in the Bouguirat area, in the Mostaganem region. Morphological characterization focused on measuring conidial size and notation of fungal microscopic characters. We also studied the effect of three temperature levels (22, 25 and 28 ºC) on mycelial growth and parasite sporulation. The length of the conidia varies from 13.65 to 16.32 μm and the width from 4.83 to 7.40 μm. Mycelial growth is promoted by temperatures of 25 and 28 ºC. The last temperature also favours an important sporulation. We were not able to identify the species by to their morphological characteristics, this is in agreement with the work of many researchers who recommend the use of molecular markers in this case. On the pathogenic level, we studied the reaction of tomato (Solanum lycopersicum L.) (var. kawa) and pepper (Capsicum frutecens) (Var. Biskra) to inoculation by the fungus. On the eighth day after inoculation, the P.D.I on pepper leaves reaches 100% for isolates CF13, CF12, CF2, TI1 and TI2. The PDI is lower for Fi2, Fi3 and Fi5, respectively 90, 40 and 93%. In the case of tomatoes, the highest P.D.I is induced by the Ti2 isolate reaching the value of 90% and the lowest by Fi3 (30%).
Keywords: agrumes; Colletotrichumsp.; caractérisation morphologique; pouvoir pathogène; citrus fruits; morphological characterization; pathogenicity